1987
DOI: 10.1007/bf00377559
|View full text |Cite
|
Sign up to set email alerts
|

Little bluestem litter dynamics in Minnesota old fields

Abstract: We studied the decay and nitrogen dynamics of little bluestem (Schizachyrium scoparium) litter in fertilized and unfertilized Minnesota old fields, using the litterbag technique. Annual decay rates and nitrogen leaching losses during the first month of decay were highly correlated with N content of litter and not with fertilizer additions. After the first month of decay, nitrogen was immobilized for at least 18 months. In contrast to decay rates and early N leaching losses, these immobilization rates were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 23 publications
1
40
2
2
Order By: Relevance
“…1), so the lack of site eVects on rates of decomposition was surprising. Previous studies investigating the role of exogenous and litter N on decomposition also have found a lack of an eVect of exogenous N supply on decomposition (McClaugherty et al 1985;Prescott 1995;Knorr et al 2005) including previous studies at Cedar Creek (Pastor et al 1987;Hobbie 2005). However, some studies investigating the eVect of N fertilization on decomposition have shown results ranging from positive (O'Connell 1994;Hobbie 2005) to negative (Fog 1988;Prescott 1995) eVects of exogenous N on rates of mass loss.…”
Section: Discussionmentioning
confidence: 87%
“…1), so the lack of site eVects on rates of decomposition was surprising. Previous studies investigating the role of exogenous and litter N on decomposition also have found a lack of an eVect of exogenous N supply on decomposition (McClaugherty et al 1985;Prescott 1995;Knorr et al 2005) including previous studies at Cedar Creek (Pastor et al 1987;Hobbie 2005). However, some studies investigating the eVect of N fertilization on decomposition have shown results ranging from positive (O'Connell 1994;Hobbie 2005) to negative (Fog 1988;Prescott 1995) eVects of exogenous N on rates of mass loss.…”
Section: Discussionmentioning
confidence: 87%
“…In some studies, increased N supply led to increased litter N concentrations (Robinson et al 1995), although opposite results have also been found (Pastor et al 1987;Aerts and De Caluwe 1997). In general, litters with higher N-concentrations decompose faster (Robinson et al 1995;Aerts 1997;Kö chy and Wilson 1997).…”
Section: Introductionmentioning
confidence: 89%
“…Thus, potentially stimulating effects of N addition on N mineralization from decomposing litter may be counteracted by interactions with secondary compounds in that litter, leading to chemical immobilization of the added N (e.g. Pastor et al 1987;Hobbie and Vitousek 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Many other studies, however reported either lowered decay rates Carreiro et al, 2000) or no significant change (McClaugherty et al, 1987;Pastor et al, 1987;Hunt et al, 1988;Prescott, 1995;Bryant et al, 1998;Carreiro et al, 2000). The objectives of this study was to evaluate whether external N inputs have an effect on litter decomposition and on C, N, Ca and P dynamics in the forest floor of a regenerating hardwood forest and whether liming can reverse these effects.…”
Section: A Long Term No3mentioning
confidence: 94%
“…However some studies have reported accelerated decay rates in litter in response to increased external nitrogen inputs (Hunt et al, 1988;Carreiro et al, 2000;Hobbie, 2000;Hobbie and Vitousek, 2000) or no significant change (McClaugherty et al, 1987;Pastor et al, 1987;Hunt et al, 1988;Prescott, 1995;Bryant et al, 1998;Carreiro et al, 2000). Generally, high doses of external nitrogen accelerate decomposition when plant tissues have low contents of lignin and other recalcitrant compounds, but decelerate decomposition rate when high lignin contents are present (Berg, 1986;Fog, 1988;Berg and Matzner, 1997).…”
Section: Treatment Effects On Litter P Dynamicsmentioning
confidence: 99%